2016
DOI: 10.1139/cjp-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

LRS Bianchi type-V universe with variable modified Chaplygin gas in a scalar–tensor theory of gravitation

Abstract: The spatially homogeneous and anisotropic LRS Bianchi type-V Universe filled with variable modified Chaplygin gas in the framework of the Brans–Dicke (Brans and Dicke. Phys. Rev. 124, 925 (1961). doi:10.1103/PhysRev.124.925) scalar–tensor theory of gravitation has been studied. To obtain a determinate solution of the field equations we have used the condition that scalar field ([Formula: see text]) is a function of average scale factor. Some physical and kinematical properties of the model are discussed. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, the jerk parameter for BT-II is independent of time. Santhi and Naidu [115], Rao et al [116], Santhi et al [117], Rao and Prasanthi [118], and Shaikh et al [119] are some of the researchers who have acquired a constant jerk parameter in their work.…”
Section: Jerk Parameter (J)mentioning
confidence: 99%
“…However, the jerk parameter for BT-II is independent of time. Santhi and Naidu [115], Rao et al [116], Santhi et al [117], Rao and Prasanthi [118], and Shaikh et al [119] are some of the researchers who have acquired a constant jerk parameter in their work.…”
Section: Jerk Parameter (J)mentioning
confidence: 99%
“…In literature it is also common to use a power-law relation between BD scalar field φ and average scale factor 'a' of the form φ = φ 0 a l [89,90], where φ 0 is a constant and l is a power index. Various authors have discussed different aspects of this form of scalar field φ and have shown that it leads to constant deceleration parameter [72,91] and also time varying deceleration parameter [92,93]. Recently, Kumar and Singh [94] have introduced a BD scalar field evolves as a logarithmic function of the average scale factor to study the evolution of holographic and new agegraphic DE models.…”
Section: Tsallis Holographic Dark Energy In Bd Theorymentioning
confidence: 99%
“…Rao et al [10] have discussed FRW holographic dark energy cosmological model in Brans-Dicke theory of gravitation. Rao and Jayasudha [11] [12] have discussed holographic dark energy model with generalized Chaplygin gas in this theory of gravitation. Rao and Prasanthi [13] have studied Bianchi type V I 0 generalized ghost pilgrim dark energy model in Brans-Dicke theory of gravitation.…”
Section: Introductionmentioning
confidence: 99%